The first phosphoramide–mercury(II) complex with a Cl2Hg–OP[N(C)(C)]3 segment. Issue 3 (25th February 2016) - Saneei, Anahid; Pourayoubi, Mehrdad; Crochet, Aurelien; Fromm, Katharina M.
Abstract : Noncovalent Hg…Cl and Hg…O interactions are discussed for a three‐coordinated T‐shaped mercury(II) complex with a phosphoric triamide ligand. Bond‐valence‐sum calculations confirm the three‐coordination mode of the Hg II atom of the complex molecule. Abstract : Mercury(II) exhibits a strong preference for linear coordination which has been attributed to relativistic effects splitting the 6 p orbitals and promoting sp hybridization. If the two ligands attached to the mercury(II) ion are weak donors, the metal ion can act as a good Lewis acid and expand its coordination number. Moreover, mercury has a special affinity for softer bases, such as S and N atoms, and has much less affinity for hard bases, such as those including an O atom. The asymmetric unit of dichlorido[tris(piperidin‐1‐yl)phosphane oxide‐κ O ]mercury(II)–dichloridomercury(II) (2/1), [HgCl2 (C5 H10 N)3 PO]2 ·[HgCl2 ], is composed of one HgCl2 (C5 H10 N)3 PO complex and one half of a discrete HgCl2 entity located on an inversion centre. The coordination environment around the Hg II centre in the complex component is a distorted T‐shape. Bond‐valence‐sum calculations confirm the three‐coordination mode of the Hg II atom of the complex molecule. The noncovalent nature of the Hg…Cl and Hg…O interactions in the structure are discussed.